Simultánní traumatická ruptura ligamentum patellae a kontralaterální ruptura m. quadriceps femoris - Hladký, Vít; Havlas, Vojtěch (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2017)
Our paper presents a unique case of a 64-year-old patient after a fall, treated with oral antidiabetic drugs for type II diabetes mellitus. Following a series of examinations, a bilateral injury was diagnosed - patellar ligament tear on the right side and rupture of quadriceps femoris muscle on the left side. It is a rare injury, complicated by simultaneous involvement of both knee joints. The used therapy consisted of a bilateral surgery followed by gradual verticalisation, first with the support of a walking frame and later with the use of forearm crutches. During the final examination, the patient demonstrated full flexion at both knees, while an extension deficit of approx. 5 degrees was still present on the left side. The right knee X-ray showed a proper position of the patella after the removal of temporary tension band wire. Although the clinical results of operative treatment of both the patellar ligament rupture and rupture of quadriceps femoris muscle are in most cases good, early operative treatment, proper technique and post-operative rehabilitation are a prerequisite for success. Key words: knee injuries, patellar ligament, quadriceps muscle, rupture.
Keywords: ruptura; Disease Management; Patellar Ligament; lidé středního věku; Rupture; lidé; Quadriceps Muscle; čtyřhlavý sval stehenní; ligamentum patellae; Middle Aged; Treatment Outcome; výsledek terapie; management nemoci; Humans